(untitled) (Western European Journal of Linguistics and Education, 2024)
The role of speech communication as a type of communicative communication and the dictionary meanings of the term "dialogue" are reflected in the article. In the sources, as well as synonymous terms used along with the term communication, the definitions of communication given by linguists and issues such as rules of communication are reflected